POPULATION DYNAMICS AND mE MANAGEMENT OF THE CoMMERCIAL SHRIMP PENAEVS SEMISULCATUS FROM THE BAY OF BENGAL - Mustaf, M G; Ali, Shahadat (Biological Sciences - PJSIR, 2003)
FiSAT programme was used to estimate population parameters of Penaeus semis11/catus from length frequency data based computer programme . Lo: and K for male and female ·were found to be 23.5 cm and 27.0 cm; and 0.8 yea(1 and 0.9 yea r- 1 respectively. The estimate provided by Wetherall plot for Lo: was 23.224 cm and 27.258 cm for male and female respectively. An additional estimate of Z/K was 4.688 for male and 5.373 for female. The growth pe1forma11ce index was 2.654 and 2.817 for male and female respectively. The annual rate of natural and fishing mortality were estimated as 1 .73, 3.47 for male and 1 .72, 2.98 for female respectively. The exploitation rates were 0.67 and 0.63 for male and female respectivel y. The selection pattern Le for male was 15.88 cm and for female 18.869 cm. Recruitment pattern suggestive was one even seasonal pulse during June, July and August. Peak recruitment appeared in July. Yield-per-recruit analysis suggested that the investigated stocks are overexploited. Yield-per-recruit isopleths suggested that length at first capture was 12.0 cm (male) and 13.52 cm (female) without depletion of spawning stock. The relationship between total length and body weight were found to be W = 0.01 167 Tl,2 8956 for male and W = 0.011028 TL2 9218 for female. Highest exploitation was observed between length class 15.0 to 19.0 cm for male and between 18.0 to 23.0 cm for female. Yield and Stock Prediction analysis suggested that the highest yield and price could be achieved by simultaneously decreasing the fishing mortality to 1.5 coefficient rate.